Evaluasi penyajian laporan keuangan sesuai pedoman umum akuntansi koperasi sektor riil - Kristianty Retnawati; Dety Mulyanti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The financial statement is a reflection of the business activities of an organization. Therefore, a financial statement must be of high quality by presenting valid and accurate information which is prepared in accordance with applicable guidelines. The purpose of this study was to determine the suitability of the financial statements of bank bjb Ziebar Consumer Cooperatives with applicable guidelines, namely Permen KUKM No. 12 of 2015. This research used qualitative methods with the type of case study research. The data analysis method used is by reducing data, presenting data, and finally drawing conclusions, withdrawals, or verification. The results of the study indicate that the presentation of the financial statements of the Bank bjb Ziebar Consumer Cooperative is not fully in accordance with the KUKM Regulation No. 12 of 2015, because there are discrepancies in the basis of recording and components in the cash flow statement, and there is a CALK component that is not presented by the Bank bjb Ziebar Consumer Cooperative. However, even so the level of conformity of the financial statements of the Ziebar bank bjb Consumer Cooperative with the KUKM Regulation No. 12 of 2015 is quite good because it reaches a percentage of 85%.